Structural Property, Immunoreactivity and Gastric Digestion Characteristics of Glycated Parvalbumin from Mandarin Fish (Siniperca chuaisi) during Microwave-Assisted Maillard Reaction - Jingjing Tai; Dan Qiao; Xue Huang; Huang Hu; Wanzheng Li; Xinle Liang; Fuming Zhang; Yanbin Lu; Hong Zhang (Foods, 2022)
This study was aimed to investigate the structural and immunological properties of parvalbumin from mandarin fish during the Maillard reaction. The microwave-assisted the Maillard reaction was optimized by orthogonal designed experiments. The results showed that the type of sugar and heating time had a significant effect on the Maillard reaction (p < 0.05). The SDS-PAGE analysis displayed that the molecular weight of parvalbumin in mandarin fish changed after being glycated with the Maillard reaction. The glycated parvalbumin was analyzed by Nano-LC-MS/MS and eleven glycation sites as well as five glycation groups were identified. By using the indirect competitive ELISA method, it was found that microwave heating gave a higher desensitization ability of mandarin fish parvalbumin than induction cooker did. In vitro gastric digestion experiments showed that microwave-heated parvalbumin was proved to be digested more easily than that cooked by induction cookers. The microwave-assisted Maillard reaction modified the structure of parvalbumin and reduced the immunoreactivity of parvalbumin of mandarin fish.